Positive electrode active material and preparation method thereof, precursor material, positive electrode plate, battery and electric equipment
By adjusting the process parameters in the co-precipitation reaction, controlling the specific surface area of the ternary precursor material, the problem of insufficient stability and circulation performance of the cathode material in the prior art is solved, and a cathode active material with high capacity and excellent circulation performance is achieved.
Patent Information
- Application Number
- CN202411945449.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, when preparing ternary precursor materials, it is difficult to accurately control the specific surface area, resulting in insufficient stability and cycling performance of the cathode material.
By adjusting the process parameters in the coprecipitation reaction, including ventilation position, oxygen content and flow coefficient, the specific surface area of the precursor material is controlled, and then a positive electrode active material with low soluble alkali content is prepared.
The high capacity and excellent circulation performance of the positive electrode active material are achieved, and the energy density and safety performance of the battery are improved.
Smart Images

Figure CN119742364A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode active material and a preparation method thereof, a precursor material, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] With the growing market demand for high-performance batteries such as high energy density and the increasing popularity of electric vehicles, the market demand for battery positive electrode materials has shown a rapid growth trend. Ternary positive electrode materials are the most promising and promising materials among the currently mass-produced positive electrode materials due to their high energy density, relatively low cost, and excellent cycle performance. In ternary positive electrode materials, the higher the nickel content, the greater the energy density of the battery, which can greatly increase the battery life after a single charge and the range of the vehicle power battery. High-nickel power batteries have solved the problem of lightweight batteries, and their space-saving capabilities are far superior to ordinary ternary batteries. At the same time, the increase in the proportion of nickel reduces the use of cobalt, which reduces production costs to a certain extent.
[0003] The specific surface area and density of the ternary precursor have a decisive influence on the performance of the positive electrode material. The positive electrode material with a smaller specific surface area has a smaller contact area with the electrolyte, which effectively inhibits the occurrence of side reactions and improves the stability and rate performance of the positive electrode material. The positive electrode material with a larger specific surface area increases the number of lithium ion transmission paths and improves the energy density and discharge energy of the positive electrode material. In the prior art, the coprecipitation method is often used to prepare the ternary precursor. For example, adding a specific amount of alkaline solution to the aging slurry can accelerate the oxidation rate of the ternary precursor slurry and shorten the aging time; introducing air into the aging system can act as an oxidant to accelerate the aging rate on the one hand, and on the other hand, the surface morphology of the ternary precursor particles in the aging system can be controlled by controlling the ventilation rate and ventilation time. This scheme can increase the specific surface area of the ternary precursor material, so that the energy density and charge and discharge performance of the final ternary lithium-ion battery are improved. However, the method of increasing the specific surface area in this scheme has limitations. By introducing alkaline solution and air, the degree of oxidation is aggravated, the fibers are refined, and the specific surface area is increased. Only ternary precursor materials with large specific surface area can be prepared. At the same time, the process of increasing the specific surface area in this scheme is the washing and aging stage of the ternary precursor, and it is not corrected in the synthesis stage. In addition, by increasing the ammonia concentration in the reaction system, the specific surface area of the ternary precursor product is greatly reduced, the tap density is increased, and the particle size distribution is reduced. The positive electrode material prepared by this scheme has a small contact area with the electrolyte, which can effectively inhibit the side reaction between the surface of the positive electrode material and the electrolyte and improve the stability of the positive electrode material. However, this scheme has limitations. It is impossible to prepare ternary precursor materials with a higher specific surface area. In addition, the increase in ammonia concentration causes the factory ammonia concentration alarm, affecting the physical and mental health of workers. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a positive electrode active material and a preparation method thereof, a precursor material, a positive electrode plate, a battery and an electrical device. The preparation method of the positive electrode active material can accurately control the specific surface area of the precursor material, and the surface of the positive electrode active material has a low soluble alkali content, a high discharge capacity and good cycle performance.
[0005] To this end, the first aspect of the present invention provides a positive electrode active material, wherein the content of surface soluble alkali of the positive electrode active material satisfies the following conditions:
[0006] 1.0≤m(Li2CO3) / m(LiOH)≤1.5;
[0007] 1700ppm≤m(Li2CO3)≤2100ppm;
[0008] 1400ppm≤m(LiOH)≤1800ppm.
[0009] The surface of the positive electrode active material provided by the present invention has a low soluble alkali content. When the positive electrode active material is used in a lithium battery, the battery can have a high capacity and excellent cycle performance.
[0010] According to an embodiment of the present invention, the content of the surface soluble alkali of the positive electrode active material satisfies at least one of the following conditions:
[0011] 3300ppm≤m(Li2CO3)+m(LiOH)≤3900ppm;
[0012] 1.0≤m(Li2CO3) / m(LiOH)≤1.2.
[0013] According to an embodiment of the present invention, the tap density of the positive electrode active material is 1.0 g / cm 3 -2.5g / cm 3 ;
[0014] and / or, the positive electrode active material D 50 3μm-6μm;
[0015] And / or, the specific surface area of the positive electrode active material is 0.2 m 2 / g-0.8m 2 / g.
[0016] According to an embodiment of the present invention, the positive electrode active material has a composition shown in Formula I:
[0017] Li c Ni x Co y Mnz M w O2 Formula I;
[0018] Among them, 0.9≤c≤1.2, 0.6≤x≤0.9, 0<y≤0.4, 0<z≤0.4, 0≤w≤0.15;
[0019] M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al.
[0020] According to an embodiment of the present invention, 1≤c≤1.1, 0.8≤x≤0.9, 0.1≤y≤0.2, and 0.1≤z≤0.2.
[0021] According to an embodiment of the present invention, M is selected from at least one of Al, Ti, Nb, V, Mg, B or Y.
[0022] The second aspect of the present invention provides a method for preparing the positive electrode active material according to the first aspect, the preparation method comprising:
[0023] A mixed salt solution containing nickel salt, cobalt salt, manganese salt, and optional M salt is prepared, and the mixed salt solution, a precipitant, and a complexing agent are contacted to perform a first reaction to obtain a first crystal nucleus, wherein the particle size of the first crystal nucleus is D 50 1.0μm-1.6μm;
[0024] Passing protective gas and air to carry out a second reaction to obtain a second crystal nucleus;
[0025] The pH value of the reaction solution is reduced to 11.2-11.5 to carry out the third reaction;
[0026] Stop the air supply and control the flow coefficient n to 0.10-0.80 to carry out the fourth reaction. 50 When the particle size is 3.5 μm-4.5 μm, the feeding is stopped to obtain the precursor material;
[0027] Mixing the precursor material with a lithium source and performing calcination to obtain the positive electrode active material;
[0028] Wherein, the second reaction satisfies the following conditions:
[0029] The ventilation position is 5cm-22cm below the liquid surface; the volume ratio N of the protective gas to the air is 0.5-4; the oxygen content A during the reaction is 1.0%-3.0%; the particle size D of the second crystal nucleus is 50 1.8μm-3.0μm;
[0030] Flow coefficient n = C 络合剂 / C 混合盐 ;
[0031] C 络合剂 is the number of moles of complexing agent added per unit time;
[0032] C 混合盐 is the number of moles of mixed salt solution added per unit time.
[0033] The present invention provides a method for preparing the aforementioned positive electrode active material, by limiting the process parameters in the coprecipitation reaction, the specific surface area of the precursor can be accurately optimized, and the positive electrode active material thus obtained has low surface soluble alkali content, high capacity and excellent cycle performance. Specifically, by adjusting the ventilation position and the depth of the liquid level, the oxygen content of the reaction environment and other conditions, the reaction process of the metal salt and the precipitant can be controlled, and then the growth rate of different crystal planes of the precursor (mainly (101) crystal plane and (001) crystal plane) can be controlled, and the thickness of the particle fiber in the material can be controlled, thereby achieving the purpose of optimizing the specific surface area of the precursor.
[0034] According to an embodiment of the present invention, the specific surface area of the second crystal core is 28m 2 / g-60m 2 / g, preferably 30m 2 / g-50m 2 / g;
[0035] and / or, bulk density is 0.4 g / cm 3 -0.8g / cm 3 , preferably 0.6 g / cm 3 -0.7g / cm 3 .
[0036] According to an embodiment of the present invention, the ventilation position is located 7 cm-17 cm below the liquid surface; the volume ratio N of the protective gas to air is 1.5-2.5; and the oxygen content A during the reaction is 2.0%-2.5%.
[0037] According to an embodiment of the present invention, the protective gas includes nitrogen.
[0038] According to an embodiment of the present invention, the flow coefficient n is 0.30-0.50.
[0039] According to an embodiment of the present invention, the calcination treatment is carried out at a temperature of 700° C.-900° C. and for a time of 10 h-20 h.
[0040] The third aspect of the present invention provides a precursor material, wherein the precursor material is a secondary particle with a core-shell structure, wherein the porosity of the core is greater than the porosity of the shell; and the diameter of the core is 40%-80% of the diameter of the precursor material;
[0041] The half-peak width FWHM of the (001) crystal plane of the precursor material measured by XRD (001) and the half maximum width FWHM of the (101) crystal plane (101) The following conditions are met:
[0042] 0.40°≤FWHM (001) ≤0.59°;
[0043] 0.50°≤FWHM (101) ≤0.65°;
[0044] 1.0≤FWHM (101) / FWHM (001) ≤1.30.
[0045] When the precursor material meets the above conditions, it indicates that the growth rate of the (101) crystal plane and the (001) crystal plane of the precursor material is controlled to achieve the regulation of the particle thickness in the material, thereby optimizing the specific surface area of the material. At the same time, limiting the ratio of the half-peak width of the two crystal planes to 1.0-1.30 indicates that the precursor material has excellent crystallinity, thereby improving the stability and cycle performance of the material.
[0046] According to an embodiment of the present invention, the precursor material satisfies at least one of the following conditions:
[0047] 0.50°≤FWHM (001) ≤0.55°;
[0048] 0.53°≤FWHM (101) ≤0.58°;
[0049] 1.08≤FWHM (101) / FWHM (001) ≤1.18.
[0050] According to an embodiment of the present invention, the specific surface area of the precursor material is 5m 2 / g-25m 2 / g, preferably 9m 2 / g-13m 2 / g;
[0051] And / or, the tap density of the precursor material is 1.5 m 2 / g-2.0m 2 / g, preferably 1.6-1.8m 2 / g;
[0052] And / or, the bulk density of the precursor material is 0.7 m 2 / g-1.1m 2 / g, preferably 0.8-1.0m 2 / g.
[0053] According to an embodiment of the present invention, the specific surface area of the core is 20m 2 / g-60m 2 / g, preferably 35m 2 / g-55m 2 / g;
[0054] and / or, bulk density is 0.4 g / cm 3 -0.8g / cm 3 , preferably 0.5g / cm 3 -0.6g / cm 3 .
[0055] According to an embodiment of the present invention, the diameter of the inner core is 60%-70% of the diameter of the precursor material.
[0056] According to an embodiment of the present invention, the precursor material has a composition shown in Formula II:
[0057] Ni x Co y Mn z M w (OH)2 Formula II;
[0058] Among them, 0.6≤x≤0.9, 0<y≤0.4, 0<z≤0.4, 0≤w≤0.15;
[0059] M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al.
[0060] According to an embodiment of the present invention, 0.5≤x≤0.9, 0.1≤y≤0.2, and 0.1≤z≤0.3.
[0061] According to an embodiment of the present invention, M is selected from at least one of Al, Ti, Nb, V, Mg, B or Y.
[0062] A fourth aspect of the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the positive electrode active material described in the first aspect or the positive electrode active material prepared by the preparation method described in the second aspect.
[0063] As a result, the electrode exhibits high capacity and excellent cycle performance in electrochemical work.
[0064] The fifth aspect of the present invention provides a battery, the battery comprising the positive electrode sheet of the fourth aspect, so that the battery has good electrochemical performance.
[0065] The sixth aspect of the present invention provides an electric device, the electric device comprising the battery according to the fifth aspect. Thus, the electric device has all the advantages of the aforementioned battery, which will not be described in detail here.
[0066] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0068] Figure 1 The different color states of the slurry in the process of preparing the positive electrode active material in Example 1 of the present invention are shown. Among them, Figure a corresponds to the slurry state in step (4); Figure b corresponds to the slurry state in step (5); Figure c corresponds to the slurry state in step (9);
[0069] Figure 2 The SEM image of the precursor prepared in Example 1 of the present invention is shown;
[0070] Figure 3 The CP diagram of the precursor prepared in Example 1 of the present invention is shown;
[0071] Figure 4 The different color states of the slurry in the process of preparing the positive electrode active material in Example 2 of the present invention are shown. Among them, Figure a corresponds to the slurry state in step (4); Figure b corresponds to the slurry state in step (5); Figure c corresponds to the slurry state in step (9);
[0072] Figure 5 The SEM image of the precursor prepared in Example 2 of the present invention is shown;
[0073] Figure 6 The CP diagram of the precursor prepared in Example 2 of the present invention is shown;
[0074] Figure 7 The different color states of the slurry in the process of preparing the positive electrode active material in Example 3 of the present invention are shown. Among them, Figure a corresponds to the slurry state in step (4); Figure b corresponds to the slurry state in step (5); Figure c corresponds to the slurry state in step (9);
[0075] Figure 8 The SEM image of the precursor prepared in Example 3 of the present invention is shown;
[0076] Fig. 9 The CP diagram of the precursor prepared in Example 3 of the present invention is shown;
[0077] Fig.10The XRD patterns of the precursors prepared in Examples 1-3 of the present invention are shown;
[0078] Fig.11 The different color states of the slurry in the process of preparing the positive electrode active material in Comparative Example 2 of the present invention are shown. Among them, Figure a corresponds to the slurry state in step (4); Figure b corresponds to the slurry state in step (5); Figure c corresponds to the slurry state in step (9);
[0079] Fig.12 The SEM image of the precursor prepared in Comparative Example 2 of the present invention is shown;
[0080] Fig.13 The CP diagram of the precursor prepared in Comparative Example 2 of the present invention is shown. DETAILED DESCRIPTION
[0081] The following embodiments of the technical solution of the present invention are described in detail. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0082] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0083] "Scope" disclosed in the present invention is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0084] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0085] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0086] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0087] A first aspect of the present invention provides a positive electrode active material, wherein the content of surface soluble alkali of the positive electrode active material satisfies the following conditions:
[0088] 1.0≤m(Li2CO3) / m(LiOH)≤1.5;
[0089] 1700ppm≤m(Li2CO3)≤2100ppm;
[0090] 1400ppm≤m(LiOH)≤1800ppm.
[0091] The surface of the positive electrode active material provided by the present invention has a low soluble alkali content. When the positive electrode active material is used in a lithium battery, the battery can have a high capacity and excellent cycle performance. Specifically, when the surface of the positive electrode active material has a high soluble alkali content, it indicates that the specific surface area of the positive electrode active material is small, resulting in a reduction in its contact area with the electrolyte, thereby affecting the migration and diffusion speed of lithium ions, reducing the charge and discharge efficiency of the battery, and further affecting the actual capacity of the battery. Therefore, the present invention limits the content of the surface soluble alkali of the positive electrode active material to a suitable range, indicating that the material has a suitable specific surface area, thereby ensuring that the battery containing the material has a high capacity and excellent cycle performance.
[0092] According to a specific embodiment of the present invention, the content of the surface soluble alkali of the positive electrode active material satisfies at least one of the following conditions:
[0093] 3300ppm≤m(Li2CO3)+m(LiOH)≤3900ppm;
[0094] 1.0≤m(Li2CO3) / m(LiOH)≤1.2.
[0095] Wherein, the content of surface soluble alkali of the positive electrode active material is obtained by testing with a potentiometric titrator.
[0096] According to a specific embodiment of the present invention, the tap density of the positive electrode active material is 1.0 g / cm 3 -2.5g / cm 3 ;
[0097] and / or, the positive electrode active material D 50 3μm-6μm;
[0098] And / or, the specific surface area of the positive electrode active material is 0.2 m 2 / g-0.8m 2 / g.
[0099] The positive electrode active material has higher compaction density and tap density and smaller specific surface area, so that the battery made of the positive electrode active material has high energy density, long cycle life, excellent safety performance, etc.
[0100] According to a specific embodiment of the present invention, the positive electrode active material has a composition shown in Formula I:
[0101] Li c Ni x Co y Mn z M w O2 Formula I;
[0102] Among them, 0.9≤c≤1.2, 0.6≤x≤0.9, 0<y≤0.4, 0<z≤0.4, 0≤w≤0.15;
[0103] M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al;
[0104] Preferably, 1≤c≤1.1, 0.8≤x≤0.9, 0.1≤y≤0.2, 0.1≤z≤0.2;
[0105] Preferably, M is selected from at least one of Al, Ti, Nb, V, Mg, B or Y.
[0106] A second aspect of the present invention provides a method for preparing the positive electrode active material according to the first aspect, the preparation method comprising:
[0107] (1) preparing a mixed salt solution containing nickel salt, cobalt salt, manganese salt, and optional M salt, contacting the mixed salt solution, a precipitant, and a complexing agent, and performing a first reaction to obtain a first crystal nucleus, wherein the particle size of the first crystal nucleus is D 50 1.0μm-1.6μm.
[0108] According to a specific embodiment of the present invention, nickel salt, cobalt salt, manganese salt and M salt are prepared into a mixed salt solution according to the molar ratio of n(Ni):n(Co):n(Mn):n(M)=x:y:z:w.
[0109] Specifically, the types of the nickel salt, cobalt salt, manganese salt, and M salt are not particularly limited, and those skilled in the art may select them according to circumstances. As some specific examples, the above metal salts may be in the form of hydrated sulfates.
[0110] According to a specific embodiment of the present invention, the types of the precipitant and the complexing agent are not particularly limited, and those skilled in the art may select them according to circumstances. As some specific examples, the precipitant includes but is not limited to sodium hydroxide, and the complexing agent includes but is not limited to ammonia water.
[0111] According to a specific embodiment of the present invention, the concentrations of the mixed salt solution, the precipitant and the complexing agent are not particularly limited, and those skilled in the art may select them according to circumstances.
[0112] According to a specific embodiment of the present invention, the concentration of the complexing agent in the reaction solution of the first reaction is controlled to be 2.7 g / L-3.0 g / L, the bench pH value is 12.25-12.30, and the content of hydroxide is 3.0 g / L-4.0 g / L. This avoids the adhesion of seed crystals in the first reaction, prevents secondary nucleation, and affects the particle size distribution of the first crystal nucleus and the specific surface area, bulk density, etc. of subsequent materials.
[0113] The benchtop pH value can be obtained by testing with a Mettler benchtop pH meter.
[0114] According to a specific embodiment of the present invention, the temperature of the first reaction is 60° C.-80° C., and the stirring speed is 50 Hz-55 Hz.
[0115] Specifically, in this step, the precipitant and the complexing agent are mixed to obtain a base solution, and the mixed salt solution is added to the base solution to perform a first reaction. The time of the first reaction is not particularly limited, for example, the time of the first reaction is 1-15 hours, and a first crystal nucleus that meets the particle size requirements is obtained. The particle size D of the first crystal nucleus 50 1.0μm-1.6μm.
[0116] (2) introducing protective gas and air to carry out a second reaction to obtain a second crystal nucleus;
[0117] The second reaction satisfies the following conditions:
[0118] The ventilation position is 5cm-22cm below the liquid surface; the volume ratio N of the protective gas and air is 0.5-4; the oxygen content A during the reaction is 1.0%-3.0%; the second crystal nucleus particle size D 50 1.8μm-3.0μm.
[0119] In this step, by introducing protective gas and air into the reaction solution and adjusting the ventilation position and the ratio of protective gas to air, the oxidation intensity of the crystal nucleus is controlled, and crystal nuclei of different particle sizes are generated to obtain second crystal nuclei of different specific surface areas and densities. At the same time, the degree of oxidation of the crystal nucleus will also be reflected in the color of the slurry, and the oxidation intensity of the crystal nucleus can be grasped by observing the color of the slurry during the reaction.
[0120] According to a specific embodiment of the present invention, the ventilation position of the protective gas and air is located 5cm-22cm below the liquid surface, and preferably the ventilation position is located 7cm-17cm below the liquid surface.
[0121] According to a specific embodiment of the present invention, the volume ratio of the protective gas to the air can be obtained by the flow ratio of the two. The flow rates of the protective gas and the air are am and 3 / h、bm 3 / h, wherein 0.1≤a≤1, 0.1≤b≤1.0, the volume ratio of the protective gas to the air is N=a / b, and N satisfies 0.5-4, preferably 1.5-2.5.
[0122] Specifically, the type of the protective gas is not particularly limited, and includes but is not limited to nitrogen.
[0123] According to a specific embodiment of the present invention, the oxygen content in the second reaction control reaction process is 1.0%-3.0%, preferably 2.0%-2.5%.
[0124] According to a specific embodiment of the present invention, the specific surface area of the second crystal core is 28m 2 / g-60m 2 / g, preferably 30m 2 / g-50m 2 / g;
[0125] and / or, bulk density is 0.4 g / cm 3 -0.8g / cm 3 , preferably 0.6 g / cm 3 -0.7g / cm 3 The precursor material thus obtained has good sphericity, avoids adhesion, and has a stable structure, thereby increasing the capacity of the positive electrode active material containing the precursor material and ensuring cycle stability.
[0126] (3) The pH value of the reaction solution is reduced to 11.2-11.5 to carry out the third reaction.
[0127] In this stage, the pH value of the reaction solution is reduced to prevent the high pH value stage from being maintained for a long time and generating more crystal nuclei. The reduction of the pH value of the reaction solution can be achieved by controlling the addition of a precipitant.
[0128] According to a specific embodiment of the present invention, the step further includes: stopping adding the precipitant to the reaction solution, and adding the precipitant again until the pH value of the reaction solution drops to 11.85-11.95, and repeating this process until the pH value of the reaction solution drops to the target range, so as to further avoid the high pH stage being maintained for a long time and generating overly large crystal nuclei.
[0129] (4) Stop the air supply and control the flow coefficient n to 0.10-0.80 to carry out the fourth reaction. 50 When the particle size is 3.5 μm-4.5 μm, the feeding is stopped to obtain the precursor material;
[0130] Flow coefficient n = C 络合剂 / C 混合盐 ;
[0131] C 络合剂 is the number of moles of complexing agent added per unit time;
[0132] C 混合盐 is the number of moles of mixed salt solution added per unit time.
[0133] This stage is the shell growth stage in the precursor material. By adjusting the flow coefficient n in this process to 0.10-0.80, the flow rate of the complexing agent is regulated, and then the thickness of the primary particles constituting the shell is adjusted. As the liquid feeding time increases, the particles generated by the reaction gradually grow, and the crystallinity continues to improve until the D 50 When the particle size is 3.5 μm-4.5 μm, the feeding is stopped to obtain the precursor material.
[0134] In this step, the particle size of the slurry can be tested at regular intervals using a laser particle size analyzer until the product D 50 Meets the requirements.
[0135] According to a specific embodiment of the present invention, in this step, the flow coefficient n is controlled to be 0.10-0.80, preferably 0.30-0.50, and the reaction pH is controlled to be 11.2-11.5 to carry out the fourth reaction.
[0136] Among them, C 络合剂 is the number of moles of complexing agent added per unit time, which can be obtained by multiplying the flow rate of the complexing agent by the molar concentration of the complexing agent. 混合盐is the number of moles of mixed salt solution added per unit time, which can be obtained by multiplying the flow rate of the mixed salt solution by the molar concentration of each metal salt and then adding them together. C 络合剂 and C 混合盐 The unit of may be mol / h, mol / min, etc., and is not particularly limited.
[0137] According to a specific embodiment of the present invention, the step further comprises: obtaining a precursor material, washing, drying and sieving to obtain a powdered product, wherein an alkaline solution and pure water may be used for alternate washing, and the filter cake may be dried and sifted.
[0138] (5) The precursor material is mixed with a lithium source and calcined to obtain the positive electrode active material.
[0139] According to a specific embodiment of the present invention, the specific type of the lithium source is not particularly limited, and those skilled in the art may select it according to actual conditions. For example, the lithium source may include at least one of lithium carbonate and lithium hydroxide.
[0140] According to a specific embodiment of the present invention, the temperature and time of the calcination treatment are not particularly limited. As some specific examples, the temperature of the calcination treatment is 700° C.-900° C., and the time is 10 h-20 h.
[0141] The third aspect of the present invention provides a precursor material, wherein the precursor material is a secondary particle with a core-shell structure, wherein the porosity of the core is greater than the porosity of the shell; and the diameter of the core is 40%-80% of the diameter of the precursor material;
[0142] The half-peak width FWHM of the (001) crystal plane of the precursor material measured by XRD (001) and the half maximum width FWHM of the (101) crystal plane (101) The following conditions are met:
[0143] 0.40°≤FWHM (001) ≤0.59°;
[0144] 0.50°≤FWHM (101) ≤0.65°;
[0145] 1.0≤FWHM (101) / FWHM (001) ≤1.30.
[0146] When the precursor material meets the above conditions, it indicates that the growth rate of the (101) crystal plane, (001) crystal plane and the core of the precursor material is controlled to achieve the regulation of the particle thickness in the material, thereby optimizing the specific surface area of the material. At the same time, limiting the ratio of the half-peak width of the two crystal planes to 1.0-1.30 indicates that the precursor material has excellent crystallinity, thereby improving the stability and cycle performance of the material.
[0147] According to a specific embodiment of the present invention, the precursor material satisfies at least one of the following conditions:
[0148] 0.50°≤FWHM (001) ≤0.55°;
[0149] 0.53°≤FWHM (101) ≤0.58°;
[0150] 1.08≤FWHM (101) / FWHM (001) ≤1.18.
[0151] According to a specific embodiment of the present invention, the specific surface area of the precursor material is 5m 2 / g-25m 2 / g, preferably 9m 2 / g-13m 2 / g;
[0152] And / or, the tap density of the precursor material is 1.5 m 2 / g-2.0m 2 / g, preferably 1.6-1.8m 2 / g;
[0153] And / or, the bulk density of the precursor material is 0.7 m 2 / g-1.1m 2 / g, preferably 0.8-1.0m 2 / g. As a result, the precursor material has a higher crystallinity.
[0154] According to a specific embodiment of the present invention, the precursor material is a secondary particle with a core-shell structure, the porosity of the inner core is greater than the porosity of the outer shell, and preferably the inner core includes fibrous sheet-like primary particles, which are staggered to form a honeycomb shape; the outer shell includes lath-like primary particles, and there are pores between the lath-like primary particles.
[0155] According to a specific embodiment of the present invention, the specific surface area of the core is 20m 2 / g-60m 2 / g, preferably 35m 2 / g-55m 2 / g;
[0156] and / or, bulk density is 0.4 g / cm 3 -0.8g / cm 3 , preferably 0.5g / cm 3 -0.6g / cm 3 .
[0157] According to a specific embodiment of the present invention, the diameter of the inner core is 60%-70% of the diameter of the precursor material.
[0158] According to a specific embodiment of the present invention, the precursor material has a composition shown in Formula II:
[0159] Ni x Co y Mn z M w (OH)2 Formula II;
[0160] Among them, 0.6≤x≤0.9, 0<y≤0.4, 0<z≤0.4, 0≤w≤0.15;
[0161] M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al;
[0162] Preferably, 0.5≤x≤0.9, 0.1≤y≤0.2, 0.1≤z≤0.3;
[0163] Preferably, M is selected from at least one of Al, Ti, Nb, V, Mg, B or Y.
[0164] A fourth aspect of the present invention provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.
[0165] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.
[0166] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.
[0167] The positive electrode active material includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.
[0168] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bind the positive electrode active material and the binder to the positive electrode current collector. The present invention does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0169] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder may include at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.
[0170] These materials are all commercially available.
[0171] The fifth aspect of the present invention provides a battery, which comprises the positive electrode sheet according to the fourth aspect of the present invention, so that the battery has high capacity and excellent cycle performance.
[0172] A battery is a battery that can be used again by recharging the active materials after discharge.
[0173] It is understandable that the battery proposed in the present invention is a lithium-ion battery.
[0174] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0175] [Negative electrode]
[0176] In the battery, the negative electrode plate may be lithium metal or a lithium-containing alloy.
[0177] In some embodiments, in order to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.
[0178] The negative electrode active material layer may also optionally include a binder, a conductive agent and other optional auxiliary agents.
[0179] As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0180] As an example, the binder may include one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0181] As examples, other optional additives may include thickening and dispersing agents (eg, sodium carboxymethylcellulose CMC-Na), and PTC thermistor materials.
[0182] [Electrolyte]
[0183] The electrolyte may include an electrolyte salt and a solvent.
[0184] As an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0185] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0186] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0187] [Isolation film]
[0188] As the above-mentioned isolation membrane, the present invention has no particular limitation and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs, for example, it can include a combination of at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0189] The sixth aspect of the present invention provides an electric device, which includes the battery described in the fifth aspect. Specifically, the battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can include but is not limited to mobile devices (such as mobile phones, laptops), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, and energy storage systems.
[0190] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0191] The relevant parameters in the following examples and comparative examples were obtained by testing using the following methods:
[0192] (1) Morphology test: Scanning electron microscope test to obtain electron microscope image (SEM image) and ion beam profile polishing image (CP image);
[0193] (2) X-ray diffraction (XRD) test: obtained by X-ray diffractometer xrd dust diffractometer test;
[0194] (3) Bulk density (AD) test: obtained by bulk density meter test;
[0195] (4) Tap density (TD) test: obtained by tap density meter test;
[0196] (5) Specific surface area (BET) test: obtained by testing with a specific surface analysis instrument;
[0197] (6) Median particle size D 50 : Obtained through Malvern 2000 test;
[0198] (7) Test of soluble alkali content on the surface of positive electrode active material: obtained by potentiometric titrator test;
[0199] (8) Electrochemical performance test: The first discharge capacity and cycle performance of the positive electrode material were measured using the button cell method. The instrument used was the Xinwei battery test cabinet (CT3008). The first charge and discharge capacity test conditions were 0.2C@3.0~4.3V, 25°C. The larger the discharge capacity, the higher the material specific capacity and the higher the energy density of the battery system. The cycle performance test conditions were 1.0C@3.0~4.5V, 25°C. The smaller the capacity decay during the cycle, the higher the material stability and the better the cycle performance of the battery system.
[0200] Example 1
[0201]
Preparation of positive electrode active materials
[0202] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0203] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0204] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0205] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2μm, and the slurry color is shown in Figure 1 Figure a in the figure. During the reaction, the solution is concentrated by sedimentation in a thickener and the supernatant is discharged;
[0206] (5) Nitrogen and air were introduced into the reaction solution. The ventilation position was 8 cm below the liquid surface in the reactor, and the nitrogen to air flow ratio was 0.8 m 3 / h:0.2m 3 / h, its volume ratio N is 4, its oxygen content A in the kettle is 1.25%, and its slurry color shows a weak oxidation state (see Figure 1 (b) In this case, the crystal nucleus size D 501.8μm, BET is 29.52m 2 / g, AD is 0.75g / cm 3 ;
[0207] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0208] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to 0.7;
[0209] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to maintain at 11.3. The flow rate of ammonia water is adjusted in time to adjust the fiber thickness by monitoring the flow coefficient.
[0210] (9) Waiting for particle size D 50 When the length reaches 4.0 μm, the liquid feeding stops and the color of the slurry becomes Figure 1 Figure c in the figure. The slurry in the kettle was washed alternately with 1 mol / L sodium hydroxide solution at 80°C and pure water. The filter cake was then placed in a disk dryer for drying at a temperature of 115°C, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., a small-ratio ternary precursor material, with a BET of 6.34 m 2 / g, TD is 1.95g / cm 3 , AD is 1.08 g / cm 3 , D 50 is 4μm. Figure 2 is the SEM image of the precursor; Figure 3 is the corresponding CP diagram;
[0211] (10) The aforementioned precursor is uniformly mixed with the lithium source LiOH; sintering is performed under air conditions at a sintering temperature of 750° C. and a sintering time of 15 h; after cooling, the mixture is crushed and sieved to obtain a lithium-ion battery ternary positive electrode active material.
[0212]
Preparation of positive electrode
[0213] The above-mentioned positive electrode active material, acetylene black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 95:2.5:2.5, coated on an aluminum foil and dried, and stamped with a pressure of 100 MPa to form a positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm.
[0214]
Preparation of negative electrode sheet
[0215] The negative electrode uses a Li metal sheet with a diameter of 17 mm and a thickness of 1 mm.
[0216]
Preparation of electrolyte
[0217] A 1 mol / L LiPF6 solution was used as the electrolyte, with an equal volume mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) as the solvent.
[0218]
Isolation film
[0219] A polyethylene porous film having a thickness of 25 μm was used as a separator.
[0220] The positive electrode sheet, separator, negative electrode sheet and electrolyte are assembled into a 2025 button cell and activated.
[0221] Example 2
[0222]
Preparation of positive electrode active materials
[0223] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0224] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0225] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0226] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the first crystal nucleus D 50 The particle size is 1.2μm, and the slurry color is shown in Figure 4 Figure a in the figure. During the reaction, the solution is concentrated by sedimentation in a thickener and the supernatant is discharged;
[0227] (5) Nitrogen and air were introduced into the reaction liquid. The ventilation position was 14 cm below the liquid surface in the reactor, and the nitrogen to air flow ratio was 0.8 m 3 / h:0.4m 3 / h, its volume ratio N is 2, its oxygen content A in the kettle is 2.25%, and its slurry color shows a medium oxidation state (see Figure 4 (b) In this case, the second crystal nucleus size D 50 2.6μm, BET is 40.52m 2 / g, AD is 0.65g / cm 3 ;
[0228] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0229] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to 0.4;
[0230] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to keep the pH in the reactor within the range of 11.3. By monitoring the flow coefficient, the ammonia flow rate is adjusted in time to adjust the fiber thickness;
[0231] (9) Waiting for particle size D 50 When the length reaches 4.0 μm, the liquid feeding stops and the color of the slurry becomes Figure 4 Figure c in the figure. The slurry in the kettle was washed alternately with 1 mol / L sodium hydroxide solution at 80°C and pure water. The filter cake was then placed in a disk dryer for drying at a temperature of 115°C, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., a medium-ratio ternary precursor material, with a BET of 10.32 m 2 / g, TD is 1.74g / cm 3 , AD is 1.01 g / cm 3 , D 50 is 4μm. Figure 5 is the SEM image of the precursor; Figure 6 is the corresponding CP diagram;
[0232] (10) The aforementioned precursor is uniformly mixed with the lithium source LiOH; sintering is performed under air conditions at a sintering temperature of 750° C. and a sintering time of 15 h; after cooling, the mixture is crushed and sieved to obtain a lithium-ion battery ternary positive electrode active material.
[0233] The preparation of the positive electrode sheet, the negative electrode sheet, the electrolyte, the selection of the separator and the assembly of the battery are the same as those in Example 1.
[0234] Example 3
[0235]
Preparation of positive electrode active materials
[0236] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0237] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0238] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0239] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2μm, and the slurry color is shown in Figure 7 Figure a in the figure. During the reaction, the solution is concentrated by sedimentation in a thickener and the supernatant is discharged;
[0240] (5) Nitrogen and air were introduced into the reaction liquid. The ventilation position was 20 cm below the liquid surface in the reactor, and the nitrogen to air flow ratio was 0.6 m 3 / h:0.8m 3 / h, its volume ratio N is 0.75, its oxygen content A in the kettle is about 2.75%, and its slurry color shows a strong oxidation state (see Figure 7 (b) In this case, the crystal nucleus size D 50 3.0μm, BET 59.52m 2 / g, AD is 0.45g / cm 3 ;
[0241] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0242] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to 0.2;
[0243] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to keep the pH in the reactor within the range of 11.3. By monitoring the flow coefficient, the ammonia flow rate is adjusted in time to adjust the fiber thickness;
[0244] (9) Waiting for particle size D 50 When the length reaches 4.0 μm, the liquid feeding stops and the color of the slurry becomes Figure 7 Figure c in the figure. The slurry in the kettle was washed alternately with 1 mol / L sodium hydroxide solution at 80°C and pure water. The filter cake was then placed in a disk dryer for drying at a temperature of 115°C, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., a large-scale ternary precursor material, with a BET of 20.52 m 2 / g, TD is 1.55g / cm 3 , AD is 0.78g / cm 3 , D 50 is 4μm. Figure 8 is the SEM image of the precursor; Fig. 9 is the corresponding CP diagram;
[0245] (10) The aforementioned precursor is uniformly mixed with a lithium source; sintering is performed under air conditions at a sintering temperature of 750° C. for 15 h; after cooling, the mixture is crushed and sieved to obtain a ternary positive electrode active material for a lithium-ion battery.
[0246] The preparation of the positive electrode sheet, the negative electrode sheet, the electrolyte, the selection of the separator and the assembly of the battery are the same as those in Example 1.
[0247] Example 4
[0248]
Preparation of positive electrode active materials
[0249] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0250] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0251] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0252] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2 μm. During the reaction, the thickener is used for sedimentation and concentration, and the supernatant is discharged;
[0253] (5) Nitrogen and air are introduced into the reaction liquid, the ventilation position is 14 cm below the liquid level in the kettle, the volume ratio of nitrogen to air N is 0.75, and the oxygen content A in the kettle is 2.67%. At this time, the crystal nucleus size D 50 2.6μm;
[0254] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0255] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to 0.4;
[0256] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to maintain at 11.3. The flow rate of ammonia water is adjusted in time to adjust the fiber thickness by monitoring the flow coefficient.
[0257] (9) Waiting for particle size D 50 Stop feeding the liquid after it grows to 4.0μm. The slurry in the kettle is washed alternately with 1mol / L sodium hydroxide solution at 80℃ and pure water. Then the filter cake is placed in a disk dryer for drying at a drying temperature of 115℃, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., a medium-ratio ternary precursor material, with a BET of 14.63m 2 / g, TD is 1.63g / cm 3 , AD is 0.83g / cm 3 , D 50 4μm;
[0258] (10) The aforementioned precursor is uniformly mixed with the lithium source LiOH; sintering is performed under air conditions at a sintering temperature of 750° C. and a sintering time of 15 h; after cooling, the mixture is crushed and sieved to obtain a lithium-ion battery ternary positive electrode active material.
[0259] Example 5
[0260]
Preparation of positive electrode active materials
[0261] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0262] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0263] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0264] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2 μm. During the reaction, the thickener is used for sedimentation and concentration, and the supernatant is discharged;
[0265] (5) Nitrogen and air were introduced into the reaction liquid. The ventilation position was 14 cm below the liquid surface in the reactor, and the nitrogen to air flow ratio was 0.8 m3 / h:0.2m 3 / h, its volume ratio N is 4, and its oxygen content A in the kettle is 1.76%. At this time, the crystal nucleus particle size D 50 2.6μm;
[0266] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0267] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to 0.4;
[0268] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to maintain at 11.3. The flow rate of ammonia water is adjusted in time to adjust the fiber thickness by monitoring the flow coefficient.
[0269] (9) Waiting for particle size D 50 Stop feeding the liquid after it grows to 4.0μm. The slurry in the kettle is washed alternately with 1mol / L sodium hydroxide solution at 80℃ and pure water. Then the filter cake is placed in a disk dryer for drying at a drying temperature of 115℃, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., a small-ratio ternary precursor material, with a BET of 8.92m 2 / g, TD is 1.84g / cm 3 , AD is 1.03 g / cm 3 , D 50 4μm;
[0270] (10) The aforementioned precursor is uniformly mixed with the lithium source LiOH; sintering is performed under air conditions at a sintering temperature of 750° C. and a sintering time of 15 h; after cooling, the mixture is crushed and sieved to obtain a lithium-ion battery ternary positive electrode active material.
[0271] Example 6
[0272]
Preparation of positive electrode active materials
[0273] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0274] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0275] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0276] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2 μm. During the reaction, the thickener is used for sedimentation and concentration, and the supernatant is discharged;
[0277] (5) Nitrogen and air are introduced into the reaction liquid, the ventilation position is 8 cm below the liquid level in the kettle, the volume ratio of nitrogen to air N is 2, and the oxygen content A in the kettle is 1.54%. At this time, the crystal nucleus particle size D 50 2.6μm;
[0278] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0279] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to 0.4;
[0280] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to maintain at 11.3. The flow rate of ammonia water is adjusted in time to adjust the fiber thickness by monitoring the flow coefficient.
[0281] (9) Waiting for particle size D 50Stop feeding the liquid after it grows to 4.0μm. The slurry in the kettle is washed alternately with 1mol / L sodium hydroxide solution at 80℃ and pure water. Then the filter cake is placed in a disk dryer for drying at a drying temperature of 115℃, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., a small-ratio ternary precursor material, with a BET of 7.45m 2 / g, TD is 1.91g / cm 3 , AD is 1.06 g / cm 3 , D 50 4μm;
[0282] (10) The aforementioned precursor is uniformly mixed with the lithium source LiOH; sintering is performed under air conditions at a sintering temperature of 750° C. and a sintering time of 15 h; after cooling, the mixture is crushed and sieved to obtain a lithium-ion battery ternary positive electrode active material.
[0283] Example 7
[0284]
Preparation of positive electrode active materials
[0285] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0286] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0287] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0288] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2 μm. During the reaction, the thickener is used for sedimentation and concentration, and the supernatant is discharged;
[0289] (5) Nitrogen and air are introduced into the reaction liquid, the ventilation position is 20 cm below the liquid level in the kettle, the volume ratio of nitrogen to air N is 2, and the oxygen content A in the kettle is 2.93%. At this time, the crystal nucleus size D 502.6μm;
[0290] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0291] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to 0.4;
[0292] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to maintain at 11.3. The flow rate of ammonia water is adjusted in time to adjust the fiber thickness by monitoring the flow coefficient.
[0293] (9) Waiting for particle size D 50 Stop feeding the liquid after it grows to 4.0μm. The slurry in the kettle is washed alternately with 1mol / L sodium hydroxide solution at 80℃ and pure water. Then the filter cake is placed in a disk dryer for drying at a drying temperature of 115℃, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., a large-ratio ternary precursor material, with a BET of 24.58m 2 / g, TD is 1.51g / cm 3 , AD is 0.73g / cm 3 , D 50 4μm;
[0294] (10) The aforementioned precursor is uniformly mixed with the lithium source LiOH; sintering is performed under air conditions at a sintering temperature of 750° C. and a sintering time of 15 h; after cooling, the mixture is crushed and sieved to obtain a lithium-ion battery ternary positive electrode active material.
[0295] Example 8
[0296]
Preparation of positive electrode active materials
[0297] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0298] (2) To 10m 38750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0299] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0300] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2 μm. During the reaction, the thickener is used for sedimentation and concentration, and the supernatant is discharged;
[0301] (5) Nitrogen and air are introduced into the reaction liquid, the ventilation position is 14 cm below the liquid level in the kettle, the volume ratio of nitrogen to air N is 2, and the oxygen content A in the kettle is 2.25%. At this time, the crystal nucleus size D 50 2.9μm;
[0302] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0303] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to 0.2;
[0304] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to maintain at 11.3. The flow rate of ammonia water is adjusted in time to adjust the fiber thickness by monitoring the flow coefficient.
[0305] (9) Waiting for particle size D 50 Stop feeding the liquid after it grows to 4.0μm. The slurry in the kettle is washed alternately with 1mol / L sodium hydroxide solution at 80℃ and pure water. Then the filter cake is placed in a disk dryer for drying at a drying temperature of 115℃, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., a medium-ratio ternary precursor material, with a BET of 13.45m 2 / g, TD is 1.66g / cm3 , AD is 0.91g / cm 3 , D 50 4μm;
[0306] (10) The aforementioned precursor is uniformly mixed with the lithium source LiOH; sintering is performed under air conditions at a sintering temperature of 750° C. and a sintering time of 15 h; after cooling, the mixture is crushed and sieved to obtain a lithium-ion battery ternary positive electrode active material.
[0307] Example 9
[0308]
Preparation of positive electrode active materials
[0309] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0310] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0311] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0312] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2 μm. During the reaction, the thickener is used for sedimentation and concentration, and the supernatant is discharged;
[0313] (5) Nitrogen and air are introduced into the reaction liquid, the ventilation position is 14 cm below the liquid level in the kettle, the volume ratio of nitrogen to air N is 2, and the oxygen content A in the kettle is 2.25%. At this time, the crystal nucleus size D 50 2.3μm;
[0314] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0315] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to 0.7; (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to maintain the pH value at 11.3. By monitoring the flow coefficient, the ammonia water flow rate is adjusted in time to adjust the fiber thickness.
[0316] (9) Waiting for particle size D 50 After the particle size reaches 4.0 μm, the liquid feeding is stopped. The slurry in the kettle is washed alternately with 1 mol / L sodium hydroxide solution at 80°C and pure water. The filter cake is then placed in a disk dryer for drying at a temperature of 115°C, and then sieved through a 400-mesh sieve to obtain a powdered product, i.e., a small-ratio ternary precursor material, with a BET of 6.73 m 2 / g, TD is 1.97g / cm 3 , AD is 1.05g / cm 3 , D 50 4μm;
[0317] (10) The aforementioned precursor is uniformly mixed with the lithium source LiOH; sintering is performed under air conditions at a sintering temperature of 750° C. and a sintering time of 15 h; after cooling, the mixture is crushed and sieved to obtain a lithium-ion battery ternary positive electrode active material.
[0318] Example 10
[0319] The precursor material, positive electrode active material and battery were prepared in the same manner as in Example 2, except that a Zr source and an Al source were also added in step (1), and the raw materials were proportioned in a molar ratio of Ni:Co:Mn:Al:Zr=88:6:6:0.5:0.5.
[0320] Embodiment 11
[0321] The precursor material, the positive electrode active material and the battery were prepared in the same manner as in Example 2, except that a Ti source was also added in step (1), and the raw materials were proportioned according to a molar ratio of Ni:Co:Mn:Ti=88:6:6:1.
[0322] Comparative Example 1
[0323]
Preparation of positive electrode active materials
[0324] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0325] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0326] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0327] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2 μm. During the reaction, the thickener is used for sedimentation and concentration, and the supernatant is discharged;
[0328] (5) Nitrogen and air are introduced into the reaction liquid, the ventilation position is 3 cm below the liquid level in the kettle, the volume ratio of nitrogen to air N is 0.25, and the oxygen content A in the kettle is 0.63%. At this time, the crystal nucleus size D 50 2.6μm;
[0329] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0330] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to about 0.4;
[0331] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to keep the pH in the reactor within the range of 11.3. By monitoring the flow coefficient, the ammonia flow rate is adjusted in time to adjust the fiber thickness;
[0332] (9) Waiting for particle size D 50 Stop feeding the liquid after it grows to 4.0μm. The slurry in the kettle is washed alternately with 1mol / L sodium hydroxide solution at 80℃ and pure water. Then the filter cake is placed in a disk dryer for drying at a drying temperature of 115℃, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., the ternary precursor material, with a BET of 3.12m 2 / g, TD is 2.64g / cm 3 , AD is 1.19 g / cm 3 , D 50 4μm;
[0333] (10) The aforementioned precursor is uniformly mixed with a lithium source; sintering is performed under air conditions at a sintering temperature of 750° C. for 15 h; after cooling, the mixture is crushed and sieved to obtain a ternary positive electrode active material for a lithium-ion battery.
[0334] The preparation of the positive electrode sheet, the negative electrode sheet, the electrolyte, the selection of the separator and the assembly of the battery are the same as those in Example 1.
[0335] Comparative Example 2
[0336]
Preparation of positive electrode active materials
[0337] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0338] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0339] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0340] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2μm, and the slurry color is shown in Fig.11 Figure a in the figure. During the reaction, the solution is concentrated by sedimentation in a thickener and the supernatant is discharged;
[0341] (5) Nitrogen and air were introduced into the reaction solution. The ventilation position was 27 cm below the liquid level in the kettle. The volume ratio of nitrogen to air was 5. The oxygen content A in the kettle was 3.47%. The color of the slurry showed an overoxidized state (see Fig.11 (b) In this case, the crystal nucleus size D 50 2.6μm;
[0342] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0343] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to about 0.4;
[0344] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to keep the pH in the reactor within the range of 11.3. By monitoring the flow coefficient, the ammonia flow rate is adjusted in time to adjust the fiber thickness;
[0345] (9) Waiting for particle size D 50 When the length reaches 4.0 μm, the liquid feeding stops and the color of the slurry becomes Fig.11 Figure c in the figure. The slurry in the kettle was washed alternately with 1 mol / L sodium hydroxide solution at 80°C and pure water. The filter cake was then placed in a disk dryer for drying at a temperature of 115°C, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., the ternary precursor material, with a BET of 29.41 m 2 / g, TD is 1.34g / cm 3 , AD is 0.61g / cm 3 , D 50 is 4μm. Fig.12 is the SEM image of the precursor; Fig.13 is the corresponding CP diagram;
[0346] (10) The aforementioned precursor is uniformly mixed with a lithium source; sintering is performed under air conditions at a sintering temperature of 750° C. for 15 h; after cooling, the mixture is crushed and sieved to obtain a ternary positive electrode active material for a lithium-ion battery.
[0347] The preparation of the positive electrode sheet, the negative electrode sheet, the electrolyte, the selection of the separator and the assembly of the battery are the same as those in Example 1.
[0348] Comparative Example 3
[0349]
Preparation of positive electrode active materials
[0350] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0351] (2) To 10m 3 8750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0352] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0353] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2 μm. During the reaction, the thickener is used for sedimentation and concentration, and the supernatant is discharged;
[0354] (5) Nitrogen and air are introduced into the reaction liquid, the ventilation position is 14 cm below the liquid level in the kettle, the volume ratio of nitrogen to air N is 2, and the oxygen content A in the kettle is 2.25%. At this time, the crystal nucleus size D 50 3.5μm;
[0355] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0356] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to about 0.05;
[0357] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to keep the pH in the reactor within the range of 11.3. By monitoring the flow coefficient, the ammonia flow rate is adjusted in time to adjust the fiber thickness;
[0358] (9) Waiting for particle size D 50 After the particle size reaches 4.0 μm, the liquid feeding is stopped. The slurry in the kettle is washed alternately with 1 mol / L sodium hydroxide solution at 80°C and pure water. The filter cake is then placed in a disk dryer for drying at a temperature of 115°C, and then sieved through a 400-mesh sieve to obtain a powdered product, i.e., the ternary precursor material, with a BET of 27.34 m 2 / g, TD is 1.31g / cm 3 , AD is 0.58g / cm 3 , D 50 4μm;
[0359] (10) The aforementioned precursor is uniformly mixed with a lithium source; sintering is performed under air conditions at a sintering temperature of 750° C. for 15 h; after cooling, the mixture is crushed and sieved to obtain a ternary positive electrode active material for a lithium-ion battery.
[0360] The preparation of the positive electrode sheet, the negative electrode sheet, the electrolyte, the selection of the separator and the assembly of the battery are the same as those in Example 1.
[0361] Comparative Example 4
[0362]
Preparation of positive electrode active materials
[0363] (1) According to the molar ratio of Ni:Co:Mn=88:6:6, NiSO4·6H2O, CoSO4·H2O, and MnSO4·H2O were weighed and dissolved in deionized water to prepare a 1.72 mol / L mixed salt solution; at the same time, 8 mol / L sodium hydroxide solution was prepared as a precipitant and 25% ammonia water was prepared as a complexing agent;
[0364] (2) To 10m 38750L of deionized water was added to the reactor to cover the upper stirring paddle. The temperature of the reactor was controlled at 70°C, and the stirring speed was set to 52Hz. The upper, middle and lower stirring paddles of the reactor were all four-blade downward pressure paddles.
[0365] (3) adding 190 L of aqueous ammonia and 75 L of sodium hydroxide solution into the reactor to prepare the bottom liquid, adjusting the aqueous ammonia concentration in the reactor to 2.85 g / L and the benchtop pH value to 12.28;
[0366] (4) The prepared mixed salt solution, sodium hydroxide solution and ammonia water are added to the reactor by a metering pump. The metal salt inlet is set to 190 L / h. The inlet of sodium hydroxide solution and ammonia water is automatically adjusted according to the pH value and ammonia concentration to carry out a coprecipitation reaction until the crystal nucleus D 50 The particle size is 1.2 μm. During the reaction, the thickener is used for sedimentation and concentration, and the supernatant is discharged;
[0367] (5) Nitrogen and air are introduced into the reaction liquid, the ventilation position is 14 cm below the liquid level in the kettle, the volume ratio of nitrogen to air N is 2, and the oxygen content A in the kettle is 2.25%. At this time, the crystal nucleus size D 50 1.5μm;
[0368] (6) After reacting for 0.5 h, turn off the alkali pump and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.90; turn on the alkali pump and continue to add liquid to the reactor for 0.5 h; turn off the alkali pump again and stop adding sodium hydroxide solution to the reactor, and the pH is adjusted down to 11.35; turn on the alkali pump and continue to add liquid to the reactor, and keep the pH at 11.3;
[0369] (7) Stop the air supply and pass nitrogen into the reactor at a flow rate of 1.0 m 3 / h. Adjust the flow rate of ammonia water and control the flow coefficient n to about 1.5;
[0370] (8) As the liquid feeding time increases, the particles generated by the reaction gradually grow larger and the crystallinity continues to improve. During the reaction process, the slurry particle size is tested every hour with a laser particle size analyzer. The pH value in the reactor is adjusted to keep the pH in the reactor within the range of 11.3. By monitoring the flow coefficient, the ammonia flow rate is adjusted in time to adjust the fiber thickness;
[0371] (9) Waiting for particle size D 50 Stop feeding the liquid after it grows to 4.0μm. The slurry in the kettle is washed alternately with 1mol / L sodium hydroxide solution at 80℃ and pure water. Then the filter cake is placed in a disk dryer for drying at a drying temperature of 115℃, and then passed through a 400-mesh sieve to obtain a powdered product, i.e., the ternary precursor material, with a BET of 4.52m 2 / g, TD is 2.37g / cm3 , AD is 1.08 g / cm 3 , D 50 4μm;
[0372] (10) The aforementioned precursor is uniformly mixed with a lithium source; sintering is performed under air conditions at a sintering temperature of 750° C. for 15 h; after cooling, the mixture is crushed and sieved to obtain a ternary positive electrode active material for a lithium-ion battery.
[0373] The preparation of the positive electrode sheet, the negative electrode sheet, the electrolyte, the selection of the separator and the assembly of the battery are the same as those in Example 1.
[0374] The structures and properties of the precursors obtained in Examples 1-11 and Comparative Examples 1-4 are shown in Table 1, and the structures and properties of the positive electrode active materials are shown in Tables 2-3.
[0375] Table 1
[0376]
[0377]
[0378] Table 1
[0379]
[0380] Table 2
[0381]
[0382]
[0383] Table 3
[0384]
[0385] Result analysis:
[0386] The method provided by the present invention can be used to obtain a precursor material with controllable specific surface area. The surface of the positive electrode active material prepared by the method has a lower soluble alkali content, and the prepared battery has a higher discharge capacity and better cycle performance.
[0387] in, Figure 2-3 , Figure 5-6 , Figure 8-9 and Figure 12-13 By comparison, it can be seen that the crystallinity of the precursor prepared in the embodiment is significantly better than that in the comparative example. Fig.10 The half-peak widths of the (001) crystal plane and the (101) crystal plane of the precursors prepared in Examples 1-3 can be measured, which combined with the data in Table 1 further demonstrates that the precursors prepared in Examples 1-11 have excellent crystallinity.
[0388] Comparative Examples 1-9 show that precursors with different specific surface areas can be obtained by changing the ventilation position in step (5), the volume ratio of nitrogen to air, the oxygen content during the reaction, and the flow coefficient in step (7). Among them, the oxygen content during the reaction is jointly affected by the ventilation position and the nitrogen / air volume ratio. The greater the difference between the ventilation position and the liquid level in the reactor, the smaller the volume ratio of nitrogen to air, and the higher the oxygen content during the reaction.
[0389] It can be seen from Table 3 that the battery performance of Example 2 is better, indicating that the specific surface area, density and other parameters of the precursor prepared in this example are more suitable. When the type of doping element is changed (ie, Examples 10-11), the prepared battery still has good electrical performance.
[0390] Compared with Example 1 and Example 2, the oxygen content in step (5) is lower. Figure 1 , Figure 4 As shown in Table 1-2, the colors of the slurries obtained in step (5) of Example 1 and Example 2 are significantly different, indicating that the adjustment of step (5) affects the oxidation degree of the reactants (Example 1 is a weak oxidation state, Example 2 is a medium oxidation state). At the same time, the flow coefficient in step (7) is large, the specific surface area of the obtained precursor is small, the density is large, and the half-peak width FWHM of the (001) crystal plane in the XRD spectrum of the precursor is (001) and the half maximum width FWHM of the (101) crystal plane (101) The ratio is large, and the surface soluble alkali content of the positive electrode active material prepared based on the precursor is high, and the corresponding battery capacity and cycle performance will decrease.
[0391] Compared with Example 2, Example 3 has a higher oxygen content in step (5). Figure 4 , Figure 7 As shown in Table 1-2, the color of the slurry obtained in step (5) of Example 3 is different from that of Example 2, indicating that the adjustment of step (5) affects the oxidation degree of the reactants (Example 2 is a medium oxidation state, and Example 3 is a strong oxidation state). At the same time, the flow coefficient in step (7) is small, the specific surface area of the obtained precursor is large, the density is small, and the half-peak width FWHM of the (001) crystal plane in the XRD spectrum of the precursor is (001) and the half maximum width FWHM of the (101) crystal plane (101) The ratio is small, the surface soluble alkali content of the positive electrode active material prepared based on the precursor is high, and the capacity and cycle performance of the battery prepared based on the precursor are reduced.
[0392] Compared with Example 2, Examples 4-7 have different oxygen contents in step (5) and the flow coefficient in step (7). In Examples 4 and 7, the oxygen contents are higher, the surface area of the obtained precursors is larger, the density is smaller, and the half-peak width FWHM of the (001) crystal plane in the XRD spectrum of the precursors is(001) and the half maximum width FWHM of the (101) crystal plane (101) The ratio is small, and the surface soluble alkali content of the positive electrode active material prepared based on the precursor is high. The battery capacity prepared based on the precursor in Example 4 is basically unchanged, but the cycle performance is reduced. Because the oxygen content in Example 7 is higher than that in Example 4, the battery capacity and cycle performance prepared in Example 7 are reduced. The oxygen content in Examples 5 and 6 is low, the specific surface area of the prepared precursor is small, the density is large, and the half-peak width FWHM of the (001) crystal plane in the XRD spectrum of the precursor is (001) and the half maximum width FWHM of the (101) crystal plane (101) The ratio is large, and the surface soluble alkali content of the positive electrode active material prepared based on this precursor is higher. The cycle performance based on the two precursors remains basically unchanged, but the capacity decreases.
[0393] Compared with Example 2, Example 9 has the following characteristics: the oxygen content in step (5) remains unchanged, the flow coefficient in step (7) increases, the specific surface area of the obtained precursor is smaller, the density is larger, and the half-peak width FWHM of the (001) crystal plane in the XRD spectrum of the precursor is (001) and the half maximum width FWHM of the (101) crystal plane (101) The ratio remains basically unchanged, the surface soluble alkali content of the positive electrode active material prepared based on the precursor remains basically unchanged, the corresponding battery cycle performance remains basically unchanged, but the capacity decreases.
[0394] Compared with Example 2, the ventilation position of Comparative Example 1 is closer to the liquid level in the reactor, the nitrogen / air volume is relatively small, the oxygen content is too low, the specific surface area of the obtained precursor is too small, the density is too large, and the half-peak width FWHM of the (001) crystal plane in the XRD spectrum of the precursor is (001) and the half maximum width FWHM of the (101) crystal plane (101) The ratio is large, the surface soluble alkali content of the positive electrode active material prepared based on the precursor is high, and the cycle performance capacity of the positive electrode active material prepared based on the precursor is reduced.
[0395] Comparative Example 2 Compared with Example 2, the ventilation position is farther than the liquid level in the reactor, the nitrogen / air volume is relatively large, and the oxygen content is too high. Figure 4 , Fig.11 As shown in Table 1-2, the color of the slurry obtained in step (5) of comparative example 2 is significantly different from that of the slurry obtained in step (5) of example 2, indicating that the adjustment of step (5) affects the oxidation degree of the reactants (example 2 is in a medium oxidation state, and comparative example 2 is in a peroxidation state). The specific surface area of the obtained precursor is too large, the density is too small, and the half-peak width FWHM of the (001) crystal plane in the XRD spectrum of the precursor is (001) and the half maximum width FWHM of the (101) crystal plane (101)The ratio is small, the surface soluble alkali content of the positive electrode active material prepared based on the precursor is high, and the cycle performance capacity of the positive electrode active material prepared based on the precursor is reduced.
[0396] Compared with Example 2, in Comparative Example 3, the flow coefficient in step (7) is too small, resulting in the precursor having a larger specific surface area and a smaller density. The surface soluble alkali content of the positive electrode active material prepared based on the precursor is high, and the cycle performance capacity of the positive electrode active material prepared based on the precursor is reduced.
[0397] Compared with Example 2, in Comparative Example 4, the flow coefficient in step (7) is too large, resulting in the specific surface area of the precursor being too small and the density being too large. The surface soluble alkali content of the positive electrode active material prepared based on the precursor is high, and the cycle performance capacity of the positive electrode active material prepared based on the precursor is reduced.
[0398] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0399] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A positive electrode active material, characterized in that: The content of surface soluble alkali of the positive electrode active material meets the following conditions: 1.0≤m(Li2CO3) / m(LiOH)≤1.5; 1700ppm≤m(Li2CO3)≤2100ppm; 1400ppm≤m(LiOH)≤1800ppm.
2. The positive electrode active material according to claim 1, characterized in that The content of the surface soluble alkali of the positive electrode active material satisfies at least one of the following conditions: 3300ppm≤m(Li2CO3)+m(LiOH)≤3900ppm; 1.0≤m(Li2CO3) / m(LiOH)≤1.
2.
3. The positive electrode active material according to claim 1, characterized in that The tap density of the positive electrode active material is 1.0 g / cm 3 -2.5g / cm 3 ; and / or, the positive electrode active material D 50 3μm-6μm; And / or, the specific surface area of the positive electrode active material is 0.2 m 2 / g-0.8m 2 / g.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The positive electrode active material has a composition shown in Formula I: Li c Ni x Co y Mn z M w O2 of formula I; Among them, 0.9≤c≤1.2, 0.6≤x≤0.9, 0<y≤0.4, 0<z≤0.4, 0≤w≤0.15; M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al; Preferably, 1≤c≤1.1, 0.8≤x≤0.9, 0.1≤y≤0.2, 0.1≤z≤0.2; Preferably, M is selected from at least one of Al, Ti, Nb, V, Mg, B or Y.
5. A method for preparing a positive electrode active material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: A mixed salt solution containing nickel salt, cobalt salt, manganese salt, and optional M salt is prepared, and the mixed salt solution, a precipitant, and a complexing agent are contacted to perform a first reaction to obtain a first crystal nucleus, wherein the particle size of the first crystal nucleus is D 50 1.0μm-1.6μm; Passing protective gas and air to carry out a second reaction to obtain a second crystal nucleus; The pH value of the reaction solution is reduced to 11.2-11.5 to carry out the third reaction; Stop the air supply and control the flow coefficient n to 0.10-0.80 to carry out the fourth reaction. 50 When the particle size is 3.5 μm-4.5 μm, the feeding is stopped to obtain the precursor material; Mixing the precursor material with a lithium source and performing calcination to obtain the positive electrode active material; Wherein, the second reaction satisfies the following conditions: The ventilation position is 5cm-22cm below the liquid surface; the volume ratio N of the protective gas and air is 0.5-4; the oxygen content A during the reaction is 1.0%-3.0%; the particle size D of the second crystal nucleus is 50 1.8μm-3.0μm; Flow coefficient n = C 络合剂 / C 混合盐 ; C 络合剂 is the number of moles of complexing agent added per unit time; C 混合盐 is the number of moles of mixed salt solution added per unit time.
6. The preparation method according to claim 5, characterized in that: The specific surface area of the second crystal core is 28m 2 / g-60m 2 / g, preferably 30m 2 / g-50m 2 / g; and / or, bulk density of 0.4 g / cm 3 -0.8g / cm 3 , preferably 0.6 g / cm 3 -0.7g / cm 3 ; Optionally, the ventilation position is located 7 cm-17 cm below the liquid surface; the volume ratio N of the protective gas to air is 1.5-2.5; the oxygen content A during the reaction is 2.0%-2.5%; Optionally, the protective gas comprises nitrogen; Optionally, the flow coefficient n is 0.30-0.
50.
7. The preparation method according to claim 5, characterized in that: The calcination treatment is carried out at a temperature of 700° C. to 900° C. and for a time of 10 h to 20 h.
8. A precursor material, characterized in that The precursor material is a secondary particle with a core-shell structure, the porosity of the core is greater than the porosity of the shell; the diameter of the core is 40%-80% of the diameter of the precursor material; The half-peak width FWHM of the (001) crystal plane of the precursor material measured by XRD (001) and the half maximum width FWHM of the (101) crystal plane (101) The following conditions are met: 0.40°≤FWHM (001) ≤0.59°; 0.50°≤FWHM (101) ≤0.65°; 1.0≤FWHM (101) / FWHM (001) ≤1.30。 9. The precursor material according to claim 8, characterized in that The precursor material satisfies at least one of the following conditions: 0.50°≤FWHM (001) ≤0.55°; 0.53°≤FWHM (101) ≤0.58°; 1.08≤FWHM (101) / FWHM (001) ≤1.18; Optionally, the specific surface area of the precursor material is 5m 2 / g-25m 2 / g, preferably 9m 2 / g-13m 2 / g; And / or, the tap density of the precursor material is 1.5 m 2 / g-2.0m 2 / g, preferably 1.6-1.8m 2 / g; And / or, the bulk density of the precursor material is 0.7 m 2 / g-1.1m 2 / g, preferably 0.8-1.0m 2 / g.
10. The precursor material according to claim 8, characterized in that The specific surface area of the core is 20m 2 / g-60m 2 / g, preferably 35m 2 / g-55m 2 / g; and / or, bulk density of 0.4 g / cm 3 -0.8g / cm 3 , preferably 0.5g / cm 3 -0.6g / cm 3 ; Optionally, the inner core has a diameter of 60%-70% of the diameter of the precursor material.
11. The precursor material according to any one of claims 8 to 10, characterized in that: The precursor material has a composition shown in Formula II: Ni x Co y Mn z M w (OH)2 of formula II; Among them, 0.6≤x≤0.9, 0<y≤0.4, 0<z≤0.4, 0≤w≤0.15; M is selected from at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B, Y and Al; Preferably, 0.5≤x≤0.9, 0.1≤y≤0.2, 0.1≤z≤0.3; Preferably, M is selected from at least one of Al, Ti, Nb, V, Mg, B or Y.
12. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 4 or the positive electrode active material prepared by the preparation method according to any one of claims 5 to 7.
13. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 12.
14. An electrical device, characterized in that: Comprising the battery of claim 13.